Changing Practice Evaluation—Stage 1 Seminoma: Outcomes With Adjuvant Treatment Versus Surveillance: Risk Factors for Recurrence and Optimizing Follow-up Protocols—Experience From a Supraregional Center - Tyrrell, Helen E.J.; Church, David N.; Joseph, Johnson; Traill, Zoe C.; Sullivan, Mark E.; Tuthill, Mark H.; Verrill, Clare L.; Pintus, Elias P.; Dallas, Nicola L.; Rogers, Paul B.; Redgwell, Jacqueline; Protheroe, Andrew S. (Clinical genitourinary cancer, 2018)
Stage 1 seminomas treated by orchiectomy (501 cases) were analyzed to identify the risk factors for recurrence and methods of relapse detection. Rete testis invasion and, more strongly, stromal rete testis invasion increased the risk of relapse. Most recurrences were identified within 2 years of surgery by routine surveillance computed tomography scans. Stage 1 seminoma is frequently cured by radical orchiectomy; however, the management strategies after this diagnosis vary in terms of the use of adjuvant treatment and the nature of the follow-up protocols. We analyzed stage 1 seminomas treated in the Thames Valley Cancer Network for outcomes to determine whether any factors are predictive of recurrence. We also studied relapses to determine the optimal follow-up schedule and protocol. Data were obtained from centers within the Thames Valley Cancer Network for a 12-year period from 2004 to 2016. We identified 501 patients with stage 1 seminoma. Relapses occurred in 6.2% of the patients receiving adjuvant treatment and 6.1% of those who did not. The only statistically significant predictive factor identified for relapse was rete testis invasion, and the risk was greater when only stromal rete invasion was included, rather than pagetoid as well. A trend was seen toward an increased risk with increased tumor size, but the difference was not statistically significant. Recurrences developed within the first 2 years after surgery in nearly 75% of cases and were identified through surveillance computed tomography scans in 54.8% of the patients. All relapses were treated curatively. Active surveillance leads to excellent outcomes for stage 1 seminoma; however, adjuvant treatment should be reserved for those with high-risk disease. Follow-up schedules should include computed tomography imaging during the first 3 years, long-term measurement of tumor markers, and mechanisms for patients to be seen promptly should symptoms of tumor recurrence occur.